2008
DOI: 10.1038/bjp.2008.15
|View full text |Cite
|
Sign up to set email alerts
|

N‐Acetylcysteine prevents ifosfamide‐induced nephrotoxicity in rats

Abstract: Background and purpose: Ifosfamide nephrotoxicity is a serious adverse effect for children undergoing cancer chemotherapy. Our recent in vitro studies have shown that the antioxidant N-acetylcysteine (NAC), which is used extensively as an antidote for paracetamol (acetaminophen) poisoning in children, protects renal tubular cells from ifosfamide-induced toxicity at a clinically relevant concentration. To further validate this observation, an animal model of ifosfamide-induced nephrotoxicity was used to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 43 publications
(59 reference statements)
5
53
0
Order By: Relevance
“…Glucose is normally reabsorbed from the kidney and negligible amounts appear in the urine whereas proteins like albumin are macromolecules and hence are readily filtered at the glomeruli. In line with other reports (Chen et al, 2008;Sener et al, 2004), we found a significant excretion of glucose and total protein in the animals that were administered carboplatin. This suggested a loss of glomerular retention and reabsorptive capacity of the kidneys.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Glucose is normally reabsorbed from the kidney and negligible amounts appear in the urine whereas proteins like albumin are macromolecules and hence are readily filtered at the glomeruli. In line with other reports (Chen et al, 2008;Sener et al, 2004), we found a significant excretion of glucose and total protein in the animals that were administered carboplatin. This suggested a loss of glomerular retention and reabsorptive capacity of the kidneys.…”
Section: Discussionsupporting
confidence: 93%
“…This is in relation to the profile of Fanconi-like syndrome in rats (Chen et al, 2008). Depletion of the antioxidant GSH allows lipid peroxidation to occur and this oxidative stress leads to the loss of functional integrity of the cell.…”
Section: Discussionmentioning
confidence: 94%
“…TBARS is an oxidative stress marker that is dependent on aging and associated with senescence in SAM mice (32,33). It is also known that lipid peroxide hampers tissue function (34). Thus, the possibility that age-dependent oxidative stress impairs tissue function and changes lipid and carbohydrate metabolism related to lifestyle diseases is plausible.…”
Section: Discussionmentioning
confidence: 99%
“…The effects on renal tissue Nephrotoxicity induced by IFO may due to the oxidative stress and free radical generation such as NO, local depletion of GSH, reduction in the level of renal SOD 53 and increased in MDA levels indicating the enhancement lipid peroxidation as a result of impaired antioxidant defense mechanism 22,23 Membrane peroxidation can lead to changes in membrane fluidity and permeability and also to enhanced rates of protein degradation, with these eventually leading to cell lysis. 54 Mohrmann et al 55 have shown that exposure of LLC-PK1 cells to IFO metabolites acrolein or chloroacetaldehyde significantly impairs several sodium-dependent transport systems and the sodium/proton antiport system.…”
Section: 50mentioning
confidence: 99%